Dom jako przestrzeń dzieciństwa i dorastania – (auto)biograficzne konteksty w pracy coachingowej - Piorunek, Magdalena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The text characterises coaching as a non-directive form of individual support. It points out that in the coaching context, the process of self-improvement and enhancing one’s individual reflections is mostly future oriented. Nevertheless, to realise, i.e. to identify and name one’s individual and interpersonal resources one often needs to think deeply of the course of one’s life in the context of time and space. In this aspect, one’s family-of-origin home is depicted as space (place, territory) where the biographical daily life occurs in the physical and interpersonal sense. The functions of home and some contexts in which home is analysed in the social and environmental psychology are underlined. Next, the text demonstrates how selected exercises that focus on analysing home as childhood and growing-up space might be used in the life-coaching activities.
Keywords: coaching; family; home; life coaching; relation space; territory